The pattern of adverse drug reactions at a National Cancer Hospital in Indonesia: Analysis of spontaneous reports from healthcare professionals - Risani Andalasia Putri, Zullies Ikawati, Fita Rahmawati, Nanang Munif Yasin, Yuri Pertamasari (Journal of Applied Pharmaceutical Science, 2024)
Drug utilization is inevitably accompanied by a high potential for adverse drug reactions (ADRs), ranging from mild to life-threatening events. Studies on the pattern of ADRs reported by healthcare professionals are still limited in Indonesia. Therefore, this study aims to evaluate spontaneous ADRs reported to the monitoring unit at a national cancer hospital in Indonesia. These reactions were assessed for causality using the Naranjo Probability Scale (NPS), while severity assessment was carried out using the NCI CTCAE V.5.0 (National Cancer Institute Common Terminology Criteria for Adverse Events version 5.0) scale. The data obtained were subjected to descriptive analysis, and a total of 553 ADRs in 280 patients reported from January 2021 to December 2022 were assessed. The results showed that the most common reactions were nausea (11.6%), vomiting (9.9%), and constipation (7.2%). In addition, morphine, docetaxel, and cisplatin were identified as the most common substances causing ADRs. Causality assessment showed that 62.4% of ADRs were “probable” and 27.8% were “definite.” Severity assessment results showed that most reactions (48.8%) were classified as grade 2 (moderate), while 29.5% were grade 1 (mild). Based on these results, the incidence of ADRs among patients was a significant concern, which required active monitoring for prompt identification and treatment.
Keywords: Adverse drug reactions, causality, severity, pharmacovigilance